2013
DOI: 10.1007/s10120-012-0230-x
|View full text |Cite
|
Sign up to set email alerts
|

Altered mucosal DNA methylation in parallel with highly active Helicobacter pylori-related gastritis

Abstract: Background Chronic inflammation triggered by Helicobacter pylori causes altered DNA methylation in stomach mucosae, which is deeply involved in gastric carcinogenesis. This study aimed to elucidate the correlation between altered mucosal DNA methylation levels and activity of H. pylori-related gastritis, because inflammatory activity shows particular correlations with the development of diffuse-type cancer. Methods Methylation levels in stomach mucosae of 78 healthy volunteers were determined by real-time meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 42 publications
2
20
0
Order By: Relevance
“…These epigenetic changes correlate with the degree of gastric inflammation and increase with the development of premalignant changes of the gastric mucosa and finally gastric neoplasia [84,85,86]. Eradication of the infection can decrease general methylation levels [87], but this effect is not consistent for all affected genes [88].…”
Section: Host-related Factorsmentioning
confidence: 99%
“…These epigenetic changes correlate with the degree of gastric inflammation and increase with the development of premalignant changes of the gastric mucosa and finally gastric neoplasia [84,85,86]. Eradication of the infection can decrease general methylation levels [87], but this effect is not consistent for all affected genes [88].…”
Section: Host-related Factorsmentioning
confidence: 99%
“…Previous studies have also investigated the background tissues of numerous other malignancies (120)(121)(122). Yoshida et al (120) examined the methylation status of CpG islands in the promoter regions of six genes and two repetitive DNA elements in the gastric mucosae, and revealed that the methylation levels were consistently increased in a stepwise manner with activity of gastric inflammation, among patients who were H. pylori-negative, or had low-or high-titers (120), and concluded that evaluating DNA methylation levels in the gastric mucosae may predict the risk of gastric cancer.…”
Section: Studies Of Molecular Changes In Hcc Background Livermentioning
confidence: 99%
“…Yoshida et al (120) examined the methylation status of CpG islands in the promoter regions of six genes and two repetitive DNA elements in the gastric mucosae, and revealed that the methylation levels were consistently increased in a stepwise manner with activity of gastric inflammation, among patients who were H. pylori-negative, or had low-or high-titers (120), and concluded that evaluating DNA methylation levels in the gastric mucosae may predict the risk of gastric cancer. Lee et al (121) evaluated promoter region methylation of the cadherin 1 (CDH1) gene in the non-neoplastic mucosae of diffuse gastric cancer and revealed there was a significantly higher methylation ratio, compared with normal non-cancerous gastric mucosae.…”
Section: Studies Of Molecular Changes In Hcc Background Livermentioning
confidence: 99%
“…26,27 In non-cancerous inflammatory tissues, altered DNA methylation is evaluated as one of the early steps towards neoplastic change. 28 During the inflammation, the accumulation of DNA methylation contributes to the development of cancer. In noncancerous gastric mucosa, the presence of genes such as THBD, LOX, HRASLS, FLNc and HAND1 in methylated form, though rarely, supports the supposition that some gastric carcinogens are likely to induce methylation.…”
Section: H Pylori and Dna Methylation In Gcmentioning
confidence: 99%